Analisis Strategi Pemasaran Pada Toko Brunei Elektronik Meulaboh Ditengah Pandemi Covid-19 - Maulidar Maulidar (Jurnal Manajemen dan Bisnis, 2021)
This study aims to analyze the sales strategy applied to the Brunei Eletronik store amidst the weakening condition of the Indonesian economy due to the covid-19 pandemic. The method in this study was carried out with a qualitative approach to analyze the marketing strategy applied by the Brunei Eletronik store with primary data sources obtained from data collection techniques through interviews, observations and literature studies. From the results of the research carried out, it is known that a number of new facts related to the strategy implemented by the Brunei Eletronik store during the Covid-19 pandemic, sales decreased at the beginning of the outbreak of the Covid-19 pandemic in Indonesia, especially the West Aceh region due to reduced community activities outside the home, but with the use of technology in business strategies to increase sales, income gradually improves and increases. From the results of data analysis and literature review, to improve marketing strategies, Brunei Eletronik stores can apply the SWOT analysis method in increasing sales in the midst of the COVID-19 pandemic.